Strategy for evaluating the status of relay protection equipment for the new generation of intelligent substations - Liu, Dapeng; Wu, Kuizhong; Guo, Zhenhua; Cui, Yunhai; Liu, Wenbin; Zhang, Jinjing (Frontiers in Energy Research, 2024)
With the rapid development of power grid, the structure and technology of the secondary system in substations are also constantly innovating. The new generation of intelligent substations has achieved online monitoring functions for secondary equipment, making some state variables of relay protection equipment become observable indicators. Based on this, this paper proposes a novel relay protection equipment status evaluation strategy. Firstly, considering the fuzziness and uncertainty of the boundary division of relay protection evaluation levels, a relay protection risk assessment method based on normal cloud model has been proposed. Then, due to the particularity of historical statistical data, a weight calculation method combining analytical hierarchy process (AHP) and entropy weight method is adopted to eliminate subjective factors in the weight calculation process. Meanwhile, the equipment operation risk level was determined by calculating the certainty of the corresponding evaluation level for each indicator. Finally, in case study, the proposed method is used to evaluate the status of relay protection equipment, and the feasibility and accuracy of this method are verified through the analysis of the results.